ER-luminal thiol/selenol-mediated regulation of Ca2+ signalling. (11th April 2016) - Appenzeller-Herzog, Christian; Simmen, Thomas
Abstract : The endoplasmic reticulum (ER) is the main cellular Ca 2+ storage unit. Among other signalling outputs, the ER can release Ca 2+ ions, which can, for instance, communicate the status of ER protein folding to the cytosol and to other organelles, in particular the mitochondria. As a consequence, ER Ca 2+ flux can alter the apposition of the ER with mitochondria, influence mitochondrial ATP production or trigger apoptosis. All aspects of ER Ca 2+ flux have emerged as processes that are intimately controlled by intracellular redox conditions. In this review, we focus on ER-luminal redox-driven regulation of Ca 2+ flux. This involves the direct reduction of disulfides within ER Ca 2+ handling proteins themselves, but also the regulated interaction of ER chaperones and oxidoreductases such as calnexin or ERp57 with them. Well-characterized examples are the activating interactions of Ero1α with inositol 1, 4, 5-trisphosphate receptors (IP3 Rs) or of selenoprotein N (SEPN1) with sarco/endoplasmic reticulum Ca 2+ transport ATPase 2 (SERCA2). The future discovery of novel ER-luminal modulators of Ca 2+ handling proteins is likely. Based on the currently available information, we describe how the variable ER redox conditions govern Ca 2+ flux from the ER.